Obstructive sleep apnea knowledge and attitudes among recent medical graduates training in Ecuador - Chérrez-Ojeda, Iván; Calderón, Juan Carlos; Fernández García, Andrea; Jeffe, Donna B.; Santoro, Ilka; Vanegas, Emanuel; Cherrez, Annia; Cano, José; Betancourt, Freddy; Simancas-Racines, Daniel (Multidisciplinary Respiratory Medicine, 2019)
Background: We aimed to assess recent Latin American medical school graduates’ knowledge and attitudes about OSA and examine whether their knowledge and attitudes about OSA differed from practicing physicians. Methods: Recent medical graduates completed the Spanish translation of the OSA Knowledge and Attitudes (OSAKA) questionnaire at the 2013 national primary-care residency-placement meeting in Ecuador. The OSAKA includes 18 knowledge and five attitudinal items about OSA. We compared recent graduates’ data with data collected in 2010–2011 from practicing physicians using chi-square tests of associations among categorical variables and analysis of variance of differences in mean knowledge and attitude scores. Unadjusted logistic regression models tested the odds that recent graduates (vs. practicing physicians) answered each item correctly. Results: Of 265 recent graduates, 138 (52.1%) were male, and mean age was 25.9 years. Although mean knowledge was low overall, scores were lower for recent graduates than for the 367 practicing physicians (53.5% vs. 60.4%; p < 0.001). Practicing physicians were significantly more likely to answer specific items correctly with one exception—recent graduates were more likely to know that < 5 apneas-hypopneas/h is normal (OR 1.47, 1. 03–2.07). Physicians in practice attributed greater importance to OSA as clinical disorder and the need for identifying patients with OSA; but recent graduates reported greater confidence in managing patients with OSA and CPAP. Conclusions: OSA-focused educational interventions during medical school should help to improve recent medical graduates’ abilities to diagnose and treat OSA. We recommend a greater number of hours of medical students’ exposure to sleep education.